1989
DOI: 10.1111/j.1540-8159.1989.tb01842.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Ablation with High Frequency Energy for Atrioventricular Junctional (AV Nodal) Reentrant Tachycardia

Abstract: We performed transcatheter AV junction ablation with high frequency energy in four patients with AV nodal reentrant tachycardia where extensive trials of several antiarrhythmic drugs failed to prevent further recurrences of tachycardia. Initially high frequency catheter ablation induced complete AV block in all patients. A recuperation of AV 1:1 conduction followed some time later, persisting in follow-up. No complications have been encountered in either the acute phase or the follow-up (from 6 to 8 months; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[38][39][40][41] Two different approaches to radiofrequency catheter modification of AV nodal reentrant tachycardia are now being used. These techniques have been able to eliminate reentry while still preserving antegrade conduction.…”
Section: Radiofrequency Catheter Ablation For Treatment Of Av Nodal Rmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41] Two different approaches to radiofrequency catheter modification of AV nodal reentrant tachycardia are now being used. These techniques have been able to eliminate reentry while still preserving antegrade conduction.…”
Section: Radiofrequency Catheter Ablation For Treatment Of Av Nodal Rmentioning
confidence: 99%
“…Initial experience with radiofrequency ablation to produce variable degrees of AV block in animals suggested that the safety and titratibility of this energy source would make it well suited for treatment of AV nodal reentry.^^"^^ Early reports on small series of patients confirmed that radiofrequency catheter ablation could be used to eliminate reentry with preservation of conduction. [38][39][40][41] Two different approaches to radiofrequency catheter modification of AV nodal reentrant tachycardia are now being used. The first technique developed was one where lesions are applied slightly anterior and proximal to the site of the maximal His electrogram'^''* ( Fig.…”
Section: Radiofrequency Catheter Ablation For Treatment Of Av Nodal Rmentioning
confidence: 99%
“…Sinus /unction was previously studied in terms of cycle lengtii, recovery time and atrial activation pattern by catheter mapping. SeveraJ discharges (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were applied for variable periods of time (maximum 1 minutej. Sinus tachycardia and/or sinus arrest during ablation conjirmed correct catheter position.…”
mentioning
confidence: 99%